Associated Factors of Cognitive Impairment 3 to 6 Months after Ischemic Stroke: a Meta-analysis - Aijie TANG, Xiujuan DAI, Xinmiao HU, Xiayun WANG, Qian WU (Zhongguo quanke yixue, 2022)
Background Expert Consensus on the Management of Cognitive Impairment after Stroke 2021 has made it clear that, post-stroke cognitive impairment (PSCI) prevalence needs to be assessed by cognitive assessment 3-6 months after stroke, but the influencing factors found by existing studies are still controversial and need the support of EBM evidence. Objective To investigate the influencing factors of cognitive impairment 3 to 6 months after ischemic stroke, to provide an evidence-based reference for the prevention and intervention of PSCI. Methods We searched databases of the Cochrane Library, PubMed, EMBase, CINAHL, Web of Science, CNKI, SinoMed, VIP and Wanfang Data for cohort studies or case-control studies about influencing factors of cognitive impairment 3 to 6 months after ischemic stroke from inception to December 2020. RevMan5.3 software was used to conduct the Meta-analysis. Results A total of 27 studies were finally included, involving 8 677 patients (4 322 with PSCI and the other 4 355 without) . Meta-analysis results demonstrated that, age〔OR=1.10, 95%CI (1.06, 1.14) , P<0.000 01〕, educational level〔OR=0.82, 95%CI (0.78, 0.85) , P<0.000 01〕, hypertension〔OR=2.69, 95%CI (1.90, 3.81) , P<0.000 01〕, diabetes〔OR=1.95, 95%CI (1.58, 2.39) , P<0.000 01〕, atrial fibrillation〔OR=2.92, 95%CI (1.92, 4.45) , P<0.000 01〕, history of stroke〔OR=2.68, 95%CI (1.95, 3.68) , P<0.000 01〕, Fazakas score〔OR=1.86, 95%CI (1.57, 2.21) , P<0.000 01〕, NIHSS score at admission〔OR=1.44, 95%CI (1.17, 1.77) , P=0.000 6〕, hyperhomocysteinemia〔OR=1.08, 95%CI (1.02, 1.14) , P=0.006〕and drinking〔OR=2.85, 95%CI (2.00, 4.04) , P<0.000 01〕 were associated with cognitive impairment 3 to 6 months after ischemic stroke. Conclusion Available evidence suggests that, age, educational level, hypertension, diabetes, atrial fibrillation, history of prior stroke, Fazakas score, NIHSS score at admission, hyperhomocysteinemia and drinking may be associated factors of cognitive impairment 3 to 6 months after ischemic stroke. To reduce the incidence of PSCI, individualized rehabilitation program is suggested to made according to the above-mentioned associated factors for PSCI in combination with the patient's details.